2020
DOI: 10.1186/s42400-020-00050-w
|View full text |Cite
|
Sign up to set email alerts
|

Review and insight on the behavioral aspects of cybersecurity

Abstract: Stories of cyber attacks are becoming a routine in which cyber attackers show new levels of intention by sophisticated attacks on networks. Unfortunately, cybercriminals have figured out profitable business models and they take advantage of the online anonymity. A serious situation that needs to improve for networks' defenders. Therefore, a paradigm shift is essential to the effectiveness of current techniques and practices. Since the majority of cyber incidents are human enabled, this shift requires expanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Organisations have formal policies, processes and procedures to guide employees in keeping the system secure. Organisations expect their employees to be compliant with them; however, the literature has long demonstrated that formal procedures themselves do not rule human behaviour (Maalem et al 2020 ). Indeed, there are many ways in which humans can configure and use a system in unexpected and/or unprotected modes and take shortcuts in the name of improving efficiency or simply being helpful, even if it implies implementing a violation (Dekker 2003 ; Gael et al 2009 ; Schultz 2005 ; Stanton et al 2005 ).…”
Section: Challenges To Cybersecuritymentioning
confidence: 99%
“…Organisations have formal policies, processes and procedures to guide employees in keeping the system secure. Organisations expect their employees to be compliant with them; however, the literature has long demonstrated that formal procedures themselves do not rule human behaviour (Maalem et al 2020 ). Indeed, there are many ways in which humans can configure and use a system in unexpected and/or unprotected modes and take shortcuts in the name of improving efficiency or simply being helpful, even if it implies implementing a violation (Dekker 2003 ; Gael et al 2009 ; Schultz 2005 ; Stanton et al 2005 ).…”
Section: Challenges To Cybersecuritymentioning
confidence: 99%
“…One way to achieve these goals is generating scientific research, such as this viewpoint, to raise awareness, provide recommendations, and try new or improved solutions. However, the current times demand web-based, easy, fast, accurate, and objective but personalized and meaningful information and education that is adapted to the situation and context and to the target population [ 24 ]. Due to the unpredictable nature of human behavior and actions, humans are an important element and the main enablers of the level of cybersecurity that each system can and will have [ 24 ].…”
Section: Required Changes In Cybersecuritymentioning
confidence: 99%
“…A mechatronic background was the starting point for the present analysis, although we have focused on software-based features as basic functionalities for security analysis. We also delimit our work on cybersecurity's technological aspect based on the understanding that social and behavioral issues must be taken into account in a more general cybersecurity framework [75].…”
Section: Introductionmentioning
confidence: 99%